Leisure services financial management - Emanuelson, David 1949- (Champaign, IL Human Kinetics, 2013)
Leisure Services Financial Management equips students and professionals with the knowledge and skills to plan, implement, analyze, and report on the financial operations of leisure service agencies, businesses, and organizations. This unique text examines financial management systems, standards, and practices in recreation, leisure, tourism, and related fields, making it an essential reference for both future and current professionals. Leisure Services Financial Management prepares students for the roles and responsibilities of entry-level to middle managers in public, private, and nonprofit sectors of the leisure service industry. Readers will learn: foundational knowledge used in economics, accounting, finance, and marketing; the technical and technological skills involved in managing the financial aspects of a leisure service agency, organization, or business; how to develop a financial management philosophy and practice ethical financial management; and interpersonal skills useful for financial managers interacting with various stakeholders on fund-raising and development initiatives. Leisure Services Financial Management presents current financial management approaches, giving students an understanding of the differences in accounting methodologies and financial report methods across the private, nonprofit, and public sectors. By examining and working with varied examples of financial reports and analyses, students gain experience in creating and interpreting a range of financial report models. Leisure Services Financial Management offers students in-depth discussion of the knowledge and skills necessary for beginning a career in the varied and dynamic leisure service industry. This foundational guide to financial management will serve as an essential resource to both future and current professionals in the leisure industry.
Chapter 1. The Leisure Services Environment ; Leisure and Leisure Services Financial Management Defined ; How Leisure Services Began in the United States ; Leisure Services Sectors ; Challenges Facing Managers Today ; Summary -- Chapter 2. Managing Resources ; Basic Economics ; Basic Finance ; Summary -- Chapter 3. The Art of Accountancy ; History of Accounting ; Accounting ; Posting Transactions ; Codes of Ethics and Conduct ; Dimensions of Complexity in Leisure Services Accounting ; Summary -- Chapter 4. The Private Sector ; How Greed and Power Affect Business Management ; Size of the Private Sector ; Focus on Customer Needs ; Making a Profit ; Debt Versus Equity ; Taking on New Owners ; Summary -- Chapter 5. Private-Sector Accounting ; Accounting Standards ; Generally Accepted Accounting Principles ; Advanced Financial Accounting Concepts ; Transparency ; Reading Important Financial Reports ; Summary -- Chapter 6. Private-Sector Reporting and Analysis ; Due Diligence ; Budgeting ; Financial Formulas ; Summary -- Chapter 7. The Nonprofit Sector ; Noncharitable and Charitable Nonprofits ; Nonprofit Charitable Status ; Fund-Raising and Donations ; Boards of Directors ; Role of the Nonprofit Manager in Fund-Raising ; Financial Challenges ; Summary -- Chapter 8. Nonprofit Accounting and Reporting ; Fund Segregation ; Fundamentals of Nonprofit Budgeting ; Federal Reporting ; Summary -- Chapter 9. The Government Sector ; Federal Government ; State Government ; Local Government ; Summary -- Chapter 10. Government-Sector Accounting ; The GASB and the FASB ; Annual Financial Reports ; Special District CAFRs ; Managing the Finances of Governmental Leisure Services ; Summary -- Chapter 11. Capital Financing and Construction Management ; Capital Assets Financial Management ; Sources of Financing for the Private Sector ; How Nonprofits Fund Capital Improvements ; How Governmental Units Fund Capital Improvements ; Financing Public Projects Through Referenda ; Managing Construction Projects ; Summary -- Chapter 12. Future Trends ; Transparency Requirements ; Online Scrutiny ; Changes in Financial Reporting ; Changes in Technology ; Focus on Revenues ; Summary.
Includes bibliographical references
Also available in print version
Keywords: Leisure industry; Service industries -- Management